Economic and financial rationale for age-friendly housing. Issue 2 (1st August 2016) - Štaube, Tatjana; Leemeijer, Benno; Geipele, Sanda; Kauškale, Linda; Geipele, Ineta; Jansen, Jeroen
Abstract : Purpose: This study aims to indicate the reasons and provide practical suggestions to financial viability of the age-friendly housing as a sustainable construction. Design/methodology/approach: The paper reviews the primary and secondary literary sources, logical approach and comparisons of real estate and socio-economic regional statistics and conducts analysis of case studies. Findings: The study contains the results from empirical analysis on the topicality of an age-friendly built environment in the scientific literature. Key principles are identified for a current early stage of the development of a concept of the age-friendly housing. A research on the current socio-economic aspects of the creation of an age-friendly built environment is made. The practical cases of the age-friendly housing are inspected. Timely developed age-friendly housings may expect growing demands, but thorough calculation on future income is required. Research limitations/implications: The research is carried on a scale of two countries – the Kingdom of the Netherlands and the Republic of Latvia. Practical implications: The paper provides new developments in construction sector of Latvia and the Netherlands in terms of intention to further scientific and practical activities. The research has to identify the socio-economic aspects and the impact and importance of those in determining the revenues of age-friendly construction. Social implications: Age-friendly construction is going to become the standard of the sustainable property development, whereby the developers and investors will not make additional investments as they are compensated up front, and society as a total gets the revenues on the long term. Once this "wheel is turning", the benefits will be permanent. Originality/value: Latvia is being analysed in comparison with the Netherlands. The authors challenged to find opportunities to both countries from the economic viability's point of view for the age-friendly housing developments.